The Dose Effect of Mangrove Leaf Extract (Rhizophora apiculata) on Anticancer Activity in HeLa Cells - Dwi Mahfud Maulana (Journal of Stem Cell Research and Tissue Engineering, 2021)
Disease cancer caused by abnormal growth of tissue where there has been an error, fast and out of control. Judging from the fact of gender, more than 270,000 women die every year caused by cervical cancer. To inhibit the growth of cancer cells, a compound is needed that causes the cell cycle to stop so that the ability of cell proliferation decreases. Alkaloid compounds can inhibit proliferation through oxidative inhibition processes that can cause cancer. Mangrove plants have potential as anticancer, antimicrobial, and antioxidant. The content of chemical compounds found in mangroves are flavonoids, steroids, alkaloids, phenolites, saponins and tannins. These compounds show high antioxidant activity and are shown to have a real relationship with the properties of the material's bioactivity against cancer cells. One of the mangrove species is Rhizophora apiculata. The purpose of this study was to determine the IC50 value produced by Rhizophora apiculata mangrove leaf extract on HeLa cell viability and to see the effect of Rhizophora apiculata mangrove leaf extract dosage on HeLa cell viability. The method used in this research is the experimental method. The research parameters included yield, proximate test, phytochemical test, toxicity test, total phenol test, cytotoxicity test and LC-MS test. The experimental design used was a simple and complex completely randomized design (CRD) with the Tukey test.The results of this study showed that the highest yield was in the ethanol extract of 5.91%, while the n-hexane and ethyl acetate extracts respectively had yields of 1.18% and 1.31%. The results of the proximate test on the water content of leaves and powder were 64.53% and 13.86%, respectively, the results of the ash content in the leaves and powder of Rhizophora apiculata were 3.94% and 8.41%, respectively. while the water content in the extract obtained the highest yield in the ethanol extract of 21.42%, while the n-hexane extract and ethyl acetate extract were 11.08% and 15.42%, respectively. For phytochemical results, it was found that n-hexane extract only contained alkaloids, flavonoids and steroids. Ethyl acetate extract contains steroid compounds. Meanwhile, the ethanol extract contains the most bioactive compounds, namely saponins, flavonoids, tannins and triterpenoids. The toxicity test using the Brine Shrimp Lethality Test (BSLT) method resulted in the lowest IC50 of ethanol extract at 49.45 ppm while the n-hexane and ethyl acetate extracts were 251.63 ppm and 920.45 ppm respectively. In the total phenol test, the n-hexane extract was 66.79 mg GAE / 100 gr, 222.97 mg GAE / 100 gr ethyl acetate extract and 929.04 mg GAE / 100 gr ethanol extract. HeLa cell cytotoxicity testing using the MTT method (3- (4,5-dimethiltiazol-2-yl) -2,5-dipheniltetra zolium bromide) assay resulted in the highest cell viability value at a dose of 125 ppm of 46.97%. As for the doses of 250 ppm, 500 ppm 1000 ppm, and 2000 ppm resulted in a percentage of viability of 42.95% 37.70% 35.82% and 32.12%, respectively. The IC50 value of Rhizophora apiculata leaf extract was 64.42 ppm. This value indicates that the Rhizophora apiculata extract is toxic to HeLa cells.